Pemanfaatan senam "si buyung" dalam meningkatkan keterampilan motorik kasar anak usia dini - Dwi Pradipta, Galih; Sundawan Suherman, Wawan; Suhartini, Bernadeta; Yuliawan, Dhedhy; Maliki, Osa (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
This research was conducted based on problems in learning in the development of physical motor skills, especially the gross motor skills of Asy Syaffa Kindergarten students. This study aims to determine the use of Si Buyung's gymnastics in improving gross motor skills in early childhood in Asy Syaffa Kindergarten. The experimental method was applied in this study by giving 14 treatments, including pretest and posttest. The research subjects were 24 students with the sampling technique, namely purposive sampling. This research instrument uses the Gross Motor Test, which consists of a 50-meter sprint test, Dodgin run, Standing Broad Jump test, Soft Ball Throw test, Wall Pass test, Medicine Ball put test. The results of hypothesis testing found that there was an effect of Si Buyung's gymnastics on the gross motor skills of early childhood. With the conclusion criteria t count > t table, 4,062 > 2,068 and the value of sig. 2-tailed 0.000 < 0.05 so that the hypothesis is accepted. So this study proves that Si Buyung's gymnastics can improve motoric movement in early childhood. The implications of this research are expected to be an alternative for kindergarten teachers as a learning approach to developing children's gross motor movements.